Atmosphere pollution modeling in the case of accident during rocket propellant transportation by trains - Biliaiev Mykola; Biliaieva Viktoriia; Kozachyna Vitalii; Berlov Oleksandr; Gunko Olena; Chernyatyeva Kateryna (MATEC Web of Conferences, 2019)
At present time, in Ukraine the intensive development of solid-propellant missiles takes place. These missiles are called «Grim», «Grim-2», etc. Transportation of rocket propellant very often is carried out by trains. In the case of accident during such transportation great amount of toxic chemicals may be emitted into atmosphere. It is very important to predict the atmosphere pollution level near railways transport corridors to obtain the realistic information about the size of possible zones of hitting. To forecast the atmosphere pollution in the case of rocket propellant burning in railway wagon numerical models have been developed. These models are developed to predict the atmosphere pollution in two scales. The first scale is the simulation of the atmosphere pollution near the railway tracks (so called “local scale”). The second scale is the simulation of the atmosphere pollution on the territory which is adjacent to the railway tracks («urban scale»). The forecast is based on the Lagrangian model of toxic chemical dispersion. The models allow also to predict acid rain formation in the case of solid propellant burning products dispersion into atmosphere. To solve the governing equations we used difference schemes of splitting. The results of numerical experiments are presented.